Does budget air travel affect the tourist experience? Conversations with Ryanair passengers - Davies, Thomas, James (2012)
This study explores the affect budget airlines have on the tourist experience. Discussion will analyse whether passengers flying with low-cost carriers believe their tourist experience has been affected by their decision to fly with a budget airline, and if so whether this effect has been mainly positive or negative. The study seeks to investigate a possible gap in academic research. Although the links between air travel and the tourism industry are discussed in academic research, the potential impact of flying on the tourist experience is not analysed in detail, either regarding budget travel or full service carriers. Fieldwork takes the form of conversations with passengers queuing to check in with Ryanair flights at East Midlands Airport in late July 2012. The conversations were based around a prepared questionnaire, aimed at gauging passenger’s general opinions on budget airlines and the tourist experience, as well as outlining key demographic information. This fieldwork is linked with theories and interpretations outlined in academic literature and research. Although this does not directly investigate our set question, useful insight is still provided regarding a number of different aspects on budget air travel, including relevant business models, pricing strategies and market segmentation. The study will also investigate the concept of the tourist experience, including how it is defined within the industry, what factors make up this concept and how they are influenced. The work discusses the idea of the ‘flying experience’ and whether this should be considered part of the tourist experience, or an entirely separate entity.